Morphological and cytogenetic description of a new species of Parasitylenchus Micoletzky, 1922 (Tylenchida, Allantonematidae) parasitizing Harmonia axyridis (Pallas, 1773) (Coleopera, Coccinellidae) in Argentina - Camino, Nora Beatriz (2019)
Parasitylenchus pseusobifurcatus sp.n. (Tylenchida, Allantonematidae) is described for the first time for Argentina as a parasite of adults of Harmonia axyridis (Pallas, 1773) (Coleopera, Coccinellidae). The new species is closed to P. bifurcatus Poinar Jr. & Steenberg, 2012, by the characteristic of having the tail tip of all vermiform females and immature males bifurcated, but they differ by the size of the gubernaculum. Its karyotype formula is described.